The Effect of Zinc Distribution for New TB Patients who Have Ethambutol Therapy Toward Visual Field Defect - Neni Daniati; Kusdiantoro Kusdiantoro; Laksmi Wulandari; Nina Mauthia; Lukisiari Agustini (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Tuberculosis is an infection disease that is caused by Mycobacterium tuberculosis. Ethambutol therapy for TB patients can cause side effect such as decreased visual acuity, visual field defect, decreased contrast sensitivity, and disturbance of colour detection. Zinc in TB patients has decreased that causes broken cell on retina ganglion and disturbance of mytochondria function. The aim of this study is the effect of zinc supplementation for new TB patients who have ethambutol therapy toward visual field defect.Methods: This study involved 40 new TB patients who have ethambutol therapy which is classified as 20 patients who have ethambutol therapy with zinc supplementation and 20 patients who have ethambutol therapy without zinc supplementation. Each patient underwent a routine examination including visual acuity using Snellen chart which is converted to LogMAR, anterior segment using slit lamp biomicroscope, non-contact tonometry for intraocular pressure examination, posterior segment using direct ophthalmoscope, and Humphrey perimetry for visual field examination which is performed three times on first time when initial patient came, first month, and second month duration.Results: This study showed no correlation between gender with visual field defect (p=0,554), there is no correlation between age with visual field defect (p=0,418), no correlation between smoking behaviour with visual field defect (p=1), no correlation between amount of meals consumption containing Zn with visual field defect (p=0,608), and also no correlation between systematic illness history with visual field defect (p=0,305). The effect of Zn treatment to visual field defect was significant with p=0,0085.Conclusion: Zinc treatment for new TB patients with ethambutol treatment may prevent visual field defect.Keywords: ethambutol, new TB patients, zinc, visual field defect